IMPROVEMENT OF COMPETITIVE ADVANTAGES IN PAGELARAN SUBDISTRICT WEAVING FABRICS THROUGH E-BUSINESS MODEL - Ahmad Faizun; Dedi Irawan (Jurnal Signaling, 2019)
The existence of computers is a very important element in human life so that it can facilitate human work. The use of computers is not only limited to educational needs, but also involves general problems such as in business services, social or other needs where human needs will be met. The purpose of this study is to facilitate the promotion or sale of Pringsewu Lampung Pagelaran woven cloth and to help improve the superiority of Pringsewu Lampung Pagelaran woven cloth to be better known outside the area online and to make it easier for consumers to order a product. The research method used is the Waterfall method. From this research, it can be concluded that with e-business web applications, the promotion and sales process can be done quickly and can improve competitive advantage in Lampung woven fabrics.